Contaminated land investigation, assessment and remediation. - Strange, Jo (ICE design and practice guide., 2008)
This guide supplements and enhances existing authoritative and competent guidance documents prepared by key government and research organisations, such as the Environment Agency, the Construction Industry Research and Information Association and the Building Research Establishment.